Telerehabilitation for Exercise Training in Pregnancy - Uzelpasaci, Esra; Ozcakar, Levent; Ozgul, Serap; Ozyuncu, Ozgur; Beksac, Mehmet Sinan; Akbayrak, Turkan (Gynecology Obstetrics & Reproductive Medicine, 2023)
OBJECTIVE: To determine the effects of exercise training on the severity of low back pain, disability, and quality of life in pregnant women followed by telerehabilitation. STUDY DESIGN: This prospective cohort study consisted of 11 pregnant women. Low back pain severity and the effect of low back pain on functionality, quality of life, and aerobic capacity were determined by the Visual Analogue Scale, Oswestry Low Back Pain Disability Questionnaire, Short Form-36 (SF-36) and 6-minute walking test, respectively. The home-based exercise regimen was designed, and telerehabilitation support was provided two days a week for a total of eight weeks. The evaluations were repeated after the exercise program and the Wilcoxon test was used to compare the pre- vs. post-treatment results. RESULTS: Physical function, physical and emotional role difficulty, pain subscale of SF-36, low back pain severity, walking distance in the 6-minute walking test, Oswestry Low Back Pain Disability Questionnaire scores seemed to have improved after the exercise program. CONCLUSION: Telerehabilitation can be an effective method of increasing the functionality and quality of life by maintaining exercise programs during pregnancy.